Assessing the Viability of the Independent Practice of Dental Hygiene – A Brief Communication - M. Miles Beach, DMD, MS, MBA; Jay D. Shulman, DMD, MA, MSPH; Glenna Johns, RDH, MS; (Blackwell Synergy, 2007)
This paper deals with the economics of the independent dental hygiene practice.